Comparison of Different Techno-Functional Properties of Raw Lemon Pomace and Lemon Pomace Powder, and Development of Nutritional Biscuits by Incorporation of Lemon Pomace Powder - Hussain, Ashiq; Kauser, Tusneem; Aslam, Jawed; Quddoos, Muhammad Yousaf; Ali, Atif; Kauser, Samina; Kabir, Khurram; Rafique, Ayesha; Noreen, Saima; Iftikhar, Khansa; Siddique, Tahira; Gorsi, Faiza Iftikhar (Universitas Sebelas Maret, 2023)
Lemon is one among the fruits of a highly respectable class known as citrus, well known for its nutritious juice and beverage products, rich with a range of micro and macro elements, and functional bioactives. After extraction of juice, the pomace left has great potential as a sustainable agricultural processing by-product, due to its vast application in the food, feed and pharma industries. Lemon pomace powder was prepared from the by-product obtained after the extraction of juice from the lemon. Dried lemon pomace powder contained fiber (60.12 g 100 g-1), moisture (10.67 g 100 g-1), protein (4.89 g 100 g-1), fat (2.17 g 100 g-1), sugar (4.81 g 100 g-1) and ash (3.21 g 100 g-1), indicating higher amounts of ash, fat and fiber contents than wheat flour. The water-holding and oil-holding capacities of lemon pomace powder were noticed 5.9 and 3.2 g, respectively. Lightness (L*) and yellowness (b*) of powder were decreased while redness (a*) was increased in powder as compared to raw pomace. Water activity was decreased, while dry matter and pH of pomace powder were significantly increased as compared to raw pomace. Microbiological analyses revealed lower mold, yeast and total viable counts in lemon pomace powder as compared to raw lemon pomace. Dried lemon pomace powder was replaced with wheat flour at concentrations of 0%, 5%, 10% and 15% in biscuits. The biscuits were evaluated for chemical and sensory properties. Data revealed that the incorporation of lemon pomace powder improved the chemical and sensory properties of biscuits significantly. Highly acceptable biscuits with good sensory properties were obtained by incorporating 10% lemon pomace powder, with the potential use of promoting health.